Respuesta :

ANSWER

A. x-8

EXPLANATION

The given functions are:

[tex]f(x) = {x}^{2} - 11x + 24[/tex]

We factor this to get,

[tex]f(x) = (x - 8)(x - 3)[/tex]

and

[tex]g(x) = x - 3[/tex]

[tex]( \frac{f}{g} )(x) = \frac{f(x)}{g(x)} [/tex]

[tex]( \frac{f}{g} )(x) = \frac{ {x}^{2} - 11x + 24}{x - 3} \: for\: x \ne3[/tex]

[tex]( \frac{f}{g} )(x) = \frac{(x - 8)(x - 3)}{x - 3} [/tex]

Cancel the common factors to get,

[tex]( \frac{f}{g} )(x) = x - 8[/tex]

Answer: OPTION A

Step-by-step explanation:

You need to divide the function f(x) by the function g(x):

Then:

[tex](\frac{f}{g})(x)=\frac{x^2-11x+24}{x-3}[/tex]

Now, you need to simplify:

Factor the numerator. Find two numbers whose sum be -11 and whose product be 24. Theses numbers are -8 and -3. Then you get:

[tex](\frac{f}{g})(x)=\frac{(x-8)(x-3)}{x-3}[/tex]

Remember that:

[tex]\frac{a}{a}=1[/tex]

Then, you get that the expresson that is equal to  [tex](\frac{f}{g})(x)[/tex] is:

 [tex](\frac{f}{g})(x)=(x-8)[/tex]

ACCESS MORE